NIMS Crispy Choco Tub / Amalin Aliesya Mohd Azmi - Mohd Azmi, Amalin Aliesya (2021)
NIMS Crispy Choco Tub by Adeliciousz company can make renewable energy a dependable option our customers. The company was founded by Tengku Norhanim Tengku Othman since October 2014. The company was started from a small business such as choco jar and now upgrade to choco tub. Crispy Choco Jar well-known businesses in Malaysia have been entered the global market such as Thailand, Brunei and Singapore. The Business Model Canvas is a strategic management an entrepreneurial tool. It allows you to describe, design challenge, invent and pivot your business model. Partners are the relationships that you have with other business, governmental or non-consumer entities that help your business model work.